2013
DOI: 10.1186/1471-2164-14-541
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptional response of Trichoderma reesei to lignocellulose using RNA sequencing and comparison with Aspergillus niger

Abstract: BackgroundA major part of second generation biofuel production is the enzymatic saccharification of lignocellulosic biomass into fermentable sugars. Many fungi produce enzymes that can saccarify lignocellulose and cocktails from several fungi, including well-studied species such as Trichoderma reesei and Aspergillus niger, are available commercially for this process. Such commercially-available enzyme cocktails are not necessarily representative of the array of enzymes used by the fungi themselves when faced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 55 publications
9
101
0
13
Order By: Relevance
“…The "GO slim" option was employed to reduce the number of functional classes. Gene ontology slim annotation results were then used as queries against the AgBase database to classify genes into to the three main categories (molecular function, biological process, and cellular component) and to be further assigned to secondary categories (Ries et al 2013).…”
Section: Reads Mapping and Annotationsmentioning
confidence: 99%
“…The "GO slim" option was employed to reduce the number of functional classes. Gene ontology slim annotation results were then used as queries against the AgBase database to classify genes into to the three main categories (molecular function, biological process, and cellular component) and to be further assigned to secondary categories (Ries et al 2013).…”
Section: Reads Mapping and Annotationsmentioning
confidence: 99%
“…Procedures for storing and cultivating T. reesei and A. niger were as previously described by Ries et al [23].…”
Section: Journal Of Fundamentals Of Renewable Energy and Applicationsmentioning
confidence: 99%
“…HSIPs include proteins such as hydrophobins and other proteins with similar functional properties. Genes that encoded HSIPs, were induced in A. niger in response to wheat straw [31], willow [68] and sugar cane bagasse [69] and in T. reesei in response to wheat straw [135]. The induction of HSIPs suggests a possible role for HSIPs in improving the efficiency of saccharification of lignocellulose.…”
Section: Hydrophobic Surface Interacting Proteins (Hsips)mentioning
confidence: 97%
“…Swollenins were also shown to aid in the amorphogenesis step during the enzymatic hydrolysis of pre-treated biomass [134]. The swollenin gene swo1 was highly induced in T. reesei when cultured with wheat straw [135]. Saloheimo et al [133] showed swo1 in T. reesei was regulated in a similar manner to cellulases with swo1 induced by cellulose, lactose, sophorose and cellobiose.…”
Section: Swolleninsmentioning
confidence: 99%